The Relationships between School Experiences and Mental Health Outcomes among Off-Reserve First Nations Youth - Anne Guevremont; Rubab Arim; Dafna Kohen (aboriginal policy studies, 2016)
First Nations youth have been shown to have higher rates of mental health problems compared to non-Aboriginal youth. This study used the 2012 Aboriginal Peoples Survey to examine the relationships between school experiences and mental health outcomes for First Nations youth living off reserve. Mental health outcomes included self-rated mental health, psychological distress, the presence of a mood or anxiety disorder, and suicide ideation. This study provides evidence that school factors can offer protective influences as well as pose risks for the mental health of off-reserve First Nations youth. Family assistance with homework, peer influences, school sports participation, and a positive school environment were associated with positive mental health outcomes for off-reserve First Nations youth over and above the associations of mental health with individual and family factors. Findings suggest considering school factors when promoting mental health in First Nations youth.